Non Diabetic and Stress Induced Hyperglycemia [SIH] in Orthopaedic Practice What do we know so Far? - Goyal, Navendu (J Clin Diagn Res, 2014)
Hyperglycemia is also seen amongst non-diabetics and can cause significant morbidity and mortality. SIH has been reported in literature and studied in relation to trauma and critically ill patients. However, literature specific to orthopaedics on this topic is very small. Further, management of hyperglycemia in such patients is still a matter of debate and no universal consensus exists regarding its management. Future studies are needed on this topic to provide appropriate management guidelines and optimal patient outcomes.